Optical and material analysis of opacified hydrophilic intraocular lenses after explantation: a laboratory study - Tandogan, Tamer; Khoramnia, Ramin; Choi, Chul Y.; Scheuerle, Alexander F.; Wenzel, Martin; Hugger, Philipp; Auffarth, Gerd U. (BMC ophthalmology, 2015)
The opacification of hydrophilic intraocular lenses (IOLs) is a very rare complication in terms of absolute numbers. We report on the analyses of opacified Euromaxx ALI313Y and ALI313 IOLs (Argonoptics, Germany) using light and scanning electron microscopy, X-ray spectroscopy and optical bench analysis.